Penguatan Pemahaman Asesmen Catatan Anekdot dan Running Record bagi Guru TK An-Nur Desa Sungai Simpang Dua Kecamatan Kampar Kiri Hilir Kabupaten Kampar - Joni Joni; Melvi Lesmana Alim; Yenda Puspita; Ade Yelda Hastriati; Zulhendri Zulhendri; Dedi Ahmadi (Universitas Pahlawan Tuanku Tambusai, 2026)
This community service activity aimed to strengthen the understanding of TK An-Nur teachers in Sungai Simpang Dua Village, Kampar Kiri Hilir District, Kampar Regency, regarding authentic assessment in early childhood education, particularly Anecdotal Records and Running Records. The activity was based on preliminary observations showing that teachers’ understanding of child development assessment techniques was not yet optimal, resulting in unsystematic documentation of children’s development. The method consisted of preliminary observation, coordination with partners, counseling, training, assessment instrument practice, mentoring, evaluation, and reflection. The materials covered early childhood assessment concepts, authentic assessment principles, procedures for preparing Anecdotal Records and Running Records, and the use of assessment results as the basis for learning follow-up. The results indicated that participants gained a better understanding of authentic assessment and began to prepare examples of Anecdotal Records and Running Records based on the cases provided. The activity also increased participants’ awareness of the importance of objective, systematic, and continuous documentation of child development.